2017
DOI: 10.1007/s10921-017-0424-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational Time Reversal for NDT Applications Using Experimental Data

Abstract: A model-based non destructive testing (NDT) method is proposed for damage identification in elastic structures, incorporating computational time reversal (TR) analysis. Identification is performed by advancing elastic wave signals, measured at discrete sensor locations, backward in time. In contrast to a previous study, which was purely numerical and employed only synthesized data, here an experimental system with displacement sensors is used to provide physical measurements at the sensor locations. The perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…In Ref. 25, which deals with a nongeophysical application, only the total signal was used. However, we have found that the use of both the total and scattered signals enhances the identification.…”
Section: Augmented Trmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 25, which deals with a nongeophysical application, only the total signal was used. However, we have found that the use of both the total and scattered signals enhances the identification.…”
Section: Augmented Trmentioning
confidence: 99%
“…In Ref. 25, TR was used to identify a hole in a small elastic plate. In this case, the measurements were obtained both from a lab experiment, and synthetically, the results of the two procedures were compared.…”
Section: Introductionmentioning
confidence: 99%
“…A full scan of the parameter space that defined the crack and its position was performed for optimization. [Lop+17] considers an experimental validation of this approach.…”
Section: Introductionmentioning
confidence: 99%